Mechanism of MAT alpha donor preference during mating-type switching of Saccharomyces cerevisiae. - Wu, X (1996)
During homothallic switching of the mating-type (MAT) gene in Saccharomyces cerevisiae, a- or alpha-specific sequences are replaced by opposite mating-type sequences copied from one of two silent donor loci, HML alpha or HMRa. The two donors lie at opposite ends of chromosome III, approximately 190 and 90 kb, respectively, from MAT. MAT alpha cells preferentially recombine with HMR, while MATa cells select HML. The mechanisms of donor selection are different for the two mating types. MATa cells, deleted for the preferred HML gene, efficiently use HMR as a donor. However, in MAT alpha cells, HML is not an efficient donor when HMR is deleted; consequently, approximately one-third of HO HML alpha MAT alpha hmr delta cells die because they fail to repair the HO endonuclease-induced double-strand break at MAT. MAT alpha donor preference depends not on the sequence differences between HML and HMR or their surrounding regions but on their chromosomal locations. Cloned HMR donors placed at three other locations to the left of MAT, on either side of the centromere, all fail to act as efficient donors. When the donor is placed 37 kb to the left of MAT, its proximity overcomes normal donor preference, but this position is again inefficiently used when additional DNA is inserted in between the donor and MAT to increase the distance to 62 kb. Donors placed to the right of MAT are efficiently recruited, and in fact a donor situated 16 kb proximal to HMR is used in preference to HMR. The cis-acting chromosomal determinants of MAT alpha preference are not influenced by the chromosomal orientation of MAT or by sequences as far as 6 kb from HMR. These data argue that there is an alpha-specific mechanism to inhibit the use of donors to the left of MAT alpha, causing the cell to recombine most often with donors to the right of MAT alpha.